International performance level in adult ice hockey: The role of the talent environment in youth - Lenze, L.; Zibung, M.; Zuber, C.; Stegmann, P.; Conzelmann, A. (Journal of Sports Sciences, 2023)
Despite a growing interest in conducive talent development environments (TDE), the relationship between TDEs and the performance level in adulthood remains unclear. Therefore, this study examined the relationship of the micro-environment of former Swiss junior national team ice hockey players with their performance level in adulthood. With quantitative, retrospective data from n = 106 players born between 1984 and 1994, patterns of four factors club, family, peer, and school were built for early (13-15 years old) and late (16-19 years old) youth. The results revealed four structurally and mainly individually stable clusters for both developmental stages in youth. The cluster of the moderately above-average supported players between 16-19 years old demonstrated above-average values in all factors of the micro-environment and are more likely to reach international playing level in adulthood, whereas the structurally weak supported players are linked to a later regional playing level. These results indicate that simultaneous support across all four factors of the micro-environment in youth (club, family, peers, and school) is important to reach an international playing level, while low support in one or more area reduces the chance thereof. Thus, creating supportive environments across the board should be considered for a successful talent development.